The Effect of Tax Sanctions, Service Quality, and Tax Socialization on Individual Taxpayer Compliance in Gianyar Regency - I Gusti Ayu Ira Puspitadewi; Ni Ketut Lely Aryani Merkusiwati (International Journal of Economics, Commerce, and Management, 2025)
This study aims to analyze the effect of tax sanctions, service quality, and tax socialization on individual taxpayer compliance. The population in this study consists of individual taxpayers registered at the Gianyar Primary Tax Office (KPP Pratama Gianyar), with a sample of 100 respondents determined using the Slovin formula. Data were collected by distributing questionnaires directly through Google Forms to respondents. The collected data were then tested and analyzed using multiple linear regression analysis with SPSS 26 for Windows. This research contributes positively to improving compliance in submitting annual tax returns (SPT) and can provide valuable input for the Gianyar Primary Tax Office regarding the importance of enforcing tax sanctions, improving service quality, and conducting effective tax socialization to encourage better annual tax reporting each year. The results of the analysis show that tax sanctions and service quality have a positive effect on individual taxpayer compliance, whereas tax socialization does not significantly affect individual taxpayer compliance.